2015
DOI: 10.1177/1753193414565322
|View full text |Cite
|
Sign up to set email alerts
|

Arm versus forearm tourniquet for carpal tunnel decompression – Which is better? A randomized controlled trial

Abstract: I. Prospective Randomized Controlled Trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…19,20 Due to the lack of intraoperative ischemia caused by the arm tourniquet, the procedure can be performed without general or regional anesthesia, allowing it to be performed with only local and truncal anesthesia and thus not requiring an anesthesiologist. 1,21 The anesthetic and surgical procedures performed without sedation were well tolerated by patients, which allowed their execution in the ambulatory surgical center with a minimal hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Due to the lack of intraoperative ischemia caused by the arm tourniquet, the procedure can be performed without general or regional anesthesia, allowing it to be performed with only local and truncal anesthesia and thus not requiring an anesthesiologist. 1,21 The anesthetic and surgical procedures performed without sedation were well tolerated by patients, which allowed their execution in the ambulatory surgical center with a minimal hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Open carpal tunnel decompression is one of the most common day case procedures in upper limb surgery and is routinely performed under local anaesthetic without sedation using an arm tourniquet to provide a clear surgical field. Whether carpal tunnel decompression surgery is performed using an arm or a forearm tourniquet has been studied with no difference in outcomes (Cousins et al., 2015). Although tourniquets are generally tolerated well by most wide-awake patients (Baguneid et al., 1997), they can be a source of additional pain during the procedure (Nagpal et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…They did not find any statistically significant differences between groups in terms of pain, physiological response, tourniquet duration, bloodless surgical area, and operation time [8]. However, Mauray et al reported that forearm tourniquet is more tolerable for patients while the duration of tourniquet is longer [9].…”
Section: Discussionmentioning
confidence: 93%
“…In patients who received tourniquets, mean time with upperarm tourniquet was found as 9.5 minutes (8-11), and mean time with forearm tourniquet was 10.11 (8)(9)(10)(11)(12) minutes. A bloodless surgical area was successfully obtained with both tourniquet methods (Group 1 and 2).…”
Section: Resultsmentioning
confidence: 99%